Inductive logic programming : 24th International Conference, ILP 2014, Nancy, France, September 14-16, 2014 : revised selected papers /: 24th International Conference, ILP 2014, Nancy, France, September 14-16, 2014 : revised selected papers. (2015) - Unknown
No abstract available